2022
DOI: 10.1002/admi.202202236
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence Spectroscopy of Complex Dendritic Au Architectures for Application in Plasmon‐Mediated Photocatalysis and as SERS Substrates

Abstract: Absorption was calculated from total transmittance T(λ) and reflectance R(λ) spectra which were taken using a PerkinElmer Lambda 1050 UVvis-NIR spectrometer equipped with an integrating sphere to collect both scattered and specular reflectance and transmittance from the surface of the sample. A PMT R6872 detector for the UV/vis wavelength range and a Peltier-cooled InGaAs detector covering the 860-1800 nm range. Numerical simulations of the CL response were performed using the graphic interface (MNPBEM-GUI fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Compared to the network grown onto silica aerogel, the observed values are comparable, yet a bit lower. Because of high nonlinear efficiencies, such a 3d structure has the potential to function as a disordered SHG reflector substrate for vast applications, among them SERS and coherent anti-Stokes Raman scattering (CARS). …”
Section: Resultsmentioning
confidence: 99%
“…Compared to the network grown onto silica aerogel, the observed values are comparable, yet a bit lower. Because of high nonlinear efficiencies, such a 3d structure has the potential to function as a disordered SHG reflector substrate for vast applications, among them SERS and coherent anti-Stokes Raman scattering (CARS). …”
Section: Resultsmentioning
confidence: 99%
“…3(a)), thus emphasizing the critical role of spectral overlap in efficiently modulating electron transfer processes. 81,82 Furthermore, below B2 eV, photoabsorption decreases, thus resulting in a negligible generation of HEs within the molecule.…”
Section: Plasmon Dynamics and Hot Electron (He) Generationmentioning
confidence: 99%
“…For instance, Fusco et al synthesized different dendritic Au architectures by varying electrodeposition time. Using the degeneration rate of methylene blue (MB) to measure the photocatalytic activity, they found that the sample with the lowest SERS intensity exhibits the highest photocatalytic efficiency [193] . Experimentally, the enhanced photochemical processes have been determined in hot spots of plasmonic nanostructures [194,195] , corroborating the theoretical results.…”
Section: Hot Spot Effectmentioning
confidence: 99%